Investigating the individual trust and school performance in semi-virtual collaboration groups. Issue 3 (7th August 2017) - Cheng, Xusen; Fu, Shixuan; Han, Yajing; Zarifis, Alex
Abstract : Purpose: The purpose of this paper is to investigate the relationship between individual trust of students in computer supported semi-virtual collaboration groups and student's performance in school. Design/methodology/approach: Longitudinal questionnaires and interviews are conducted during the case study. By analyzing the data from the questionnaires and the grade earned by the students, the sample students are ranked with respect to the trust level and individual performance. Furthermore, the Wilcoxon signed-rank test is used to compare individual trust level and performance in the computer supported semi-virtual collaborative environment. Findings: The distribution of an individual's trust level is roughly consistent with the distribution of the individual's performance in the collaboration. Besides, the relationship between a student's trust level and the student's performance is positively correlated. Research limitations/implications: This study integrates the issues of trust, school performance, and collaboration in an educational context. Furthermore, the conclusions drawn from this paper extend the literature of multiple disciplines including education, management, and psychology. Practical implications: The conclusions could apply in the fields of education and management since the analysis revealed the relationship between an individual's trust level and their performance. Originality/value: This study contributes to the field of trust and collaboration research with a link to trust development and performance. The study also provides an insight into how to successfully improve the performance of student semi-virtual collaboration groups.